AN INTERMEDIATE COURSE IN ENGLISH FOR COMPUTING - Carbonell Olivares, María (Académica, 2011)
This textbook reviews grammar and vocabulary at an intermediate level, and expands on them to help you to find your way about the English used in the field of computing. Is organized in two sections. The first one consists of a collection of reading texts with a variety of tasks, such as comprehension, vocabulary and translation. Most of them have been especially written for language learners, but some authentic texts have also been included. The second part focuses on work on some crucial language topics. Reading tasks provide practice of reading strategies, but also of technical and semi-technical vocabulary. This textbook also pays special attention to grammatical structures which are typical of the written language, as most students of computing will have to read texts in English at some time during their degree courses.